Associations of Parental Influences with Physical Activity and Screen Time among Young Children: A Systematic Review - Huilan Xu; Li Ming Wen; Chris Rissel (Journal of Obesity)
Parents play a critical role in developing and shaping their children’s physical activity (PA) and sedentary behaviours, particularly in the early years of life. The aim of this systematic review is to identify current literature investigating associations of parental influences with both PA and screen time in young children. This systematic review was conducted in November 2013 using 6 electronic databases covering research literature from January 1998 to November 2013. Thirty articles that met inclusion criteria were identified. These studies covered five important aspects of parenting: (1) parenting practices; (2) parents’ role modelling; (3) parental perceptions of children’s PA and screen viewing behaviours; (4) parental self-efficacy; and (5) general parenting style. Findings suggest that parents’ encouragement and support can increase children’s PA, and reducing parents’ own screen time can lead to decreased child screen time. Improving parenting practices, parental self-efficacy or changing parenting style may also be promising approaches to increasing PA time and decreasing screen time of young children.